2008
DOI: 10.1002/pmic.200700770
|View full text |Cite
|
Sign up to set email alerts
|

Identification and distribution of thioredoxin‐like 2 as the antigen for the monoclonal antibody MC3 specific to colorectal cancer

Abstract: MC3 is a colorectal cancer (CRC)-specific mAb previously prepared in our laboratory that can detect CRC with high sensitivity and specificity. However, the target antigen for MC3 had not been identified due to technological limitations. In the present study, immunocytochemistry and immunohistochemistry revealed the expression patterns of MC3 antigen (MC3-Ag) in colon cancer cell lines and CRC tissues. Western blotting analysis showed that the MC3 antibody reproducibly recognized two approximately 30 kDa protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…As shown in Table 1, the increased Txl-2 expression also correlated with tumor stages consisting of tumor size (T) ( p < 0.001), lymph node invasion (N) ( p < 0.001), and distant metastasis (M) ( p = 0.022). To determine whether Txl-2 isoforms have differential expression rates, a semiquantitative reverse transcription polymerase chain reaction (RT-PCR) analysis was performed in 50 pairs of colon cancer samples using the method we reported previously (25). We found that Txl-2b was the most frequently presented Txl-2 isoform in tumor tissues (88%, 44/50), as compared to Txl-2a (8%, 4/50, p < 0.001) and Txl-2c (20%, 10/50, p < 0.001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Table 1, the increased Txl-2 expression also correlated with tumor stages consisting of tumor size (T) ( p < 0.001), lymph node invasion (N) ( p < 0.001), and distant metastasis (M) ( p = 0.022). To determine whether Txl-2 isoforms have differential expression rates, a semiquantitative reverse transcription polymerase chain reaction (RT-PCR) analysis was performed in 50 pairs of colon cancer samples using the method we reported previously (25). We found that Txl-2b was the most frequently presented Txl-2 isoform in tumor tissues (88%, 44/50), as compared to Txl-2a (8%, 4/50, p < 0.001) and Txl-2c (20%, 10/50, p < 0.001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, an increased expression of Trx-1 in CRC has 1 been shown to be associated with poor prognosis in patients with liver metastasis (30). We have recently demonstrated an increased expression of Txl-2 in colon cancer (25), but its specific role in colon cancer and the underlying mechanisms are still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations